Average Error: 0.1 → 0
Time: 21.7s
Precision: 64
$-\left(\left(bz - az\right) - \frac{vz}{vx} \cdot \left(bx - ax\right)\right)$
$-\left(\left(bz - az\right) - \frac{\sqrt[3]{vz} \cdot \sqrt[3]{vz}}{\sqrt[3]{vx} \cdot \sqrt[3]{vx}} \cdot \left(\frac{\sqrt[3]{vz}}{\sqrt[3]{vx}} \cdot \left(bx - ax\right)\right)\right)$
-\left(\left(bz - az\right) - \frac{vz}{vx} \cdot \left(bx - ax\right)\right)
-\left(\left(bz - az\right) - \frac{\sqrt[3]{vz} \cdot \sqrt[3]{vz}}{\sqrt[3]{vx} \cdot \sqrt[3]{vx}} \cdot \left(\frac{\sqrt[3]{vz}}{\sqrt[3]{vx}} \cdot \left(bx - ax\right)\right)\right)
double f(double bz, double az, double vz, double vx, double bx, double ax) {
double r2371225 = bz;
double r2371226 = az;
double r2371227 = r2371225 - r2371226;
double r2371228 = vz;
double r2371229 = vx;
double r2371230 = r2371228 / r2371229;
double r2371231 = bx;
double r2371232 = ax;
double r2371233 = r2371231 - r2371232;
double r2371234 = r2371230 * r2371233;
double r2371235 = r2371227 - r2371234;
double r2371236 = -r2371235;
return r2371236;
}


double f(double bz, double az, double vz, double vx, double bx, double ax) {
double r2371237 = bz;
double r2371238 = az;
double r2371239 = r2371237 - r2371238;
double r2371240 = vz;
double r2371241 = cbrt(r2371240);
double r2371242 = r2371241 * r2371241;
double r2371243 = vx;
double r2371244 = cbrt(r2371243);
double r2371245 = r2371244 * r2371244;
double r2371246 = r2371242 / r2371245;
double r2371247 = r2371241 / r2371244;
double r2371248 = bx;
double r2371249 = ax;
double r2371250 = r2371248 - r2371249;
double r2371251 = r2371247 * r2371250;
double r2371252 = r2371246 * r2371251;
double r2371253 = r2371239 - r2371252;
double r2371254 = -r2371253;
return r2371254;
}



# Try it out

Your Program's Arguments

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.1

$-\left(\left(bz - az\right) - \frac{vz}{vx} \cdot \left(bx - ax\right)\right)$
2. Using strategy rm
3. Applied add-cube-cbrt0.1

$\leadsto -\left(\left(bz - az\right) - \frac{vz}{\color{blue}{\left(\sqrt[3]{vx} \cdot \sqrt[3]{vx}\right) \cdot \sqrt[3]{vx}}} \cdot \left(bx - ax\right)\right)$
4. Applied add-cube-cbrt0.1

$\leadsto -\left(\left(bz - az\right) - \frac{\color{blue}{\left(\sqrt[3]{vz} \cdot \sqrt[3]{vz}\right) \cdot \sqrt[3]{vz}}}{\left(\sqrt[3]{vx} \cdot \sqrt[3]{vx}\right) \cdot \sqrt[3]{vx}} \cdot \left(bx - ax\right)\right)$
5. Applied times-frac0.1

$\leadsto -\left(\left(bz - az\right) - \color{blue}{\left(\frac{\sqrt[3]{vz} \cdot \sqrt[3]{vz}}{\sqrt[3]{vx} \cdot \sqrt[3]{vx}} \cdot \frac{\sqrt[3]{vz}}{\sqrt[3]{vx}}\right)} \cdot \left(bx - ax\right)\right)$
6. Applied associate-*l*0

$\leadsto -\left(\left(bz - az\right) - \color{blue}{\frac{\sqrt[3]{vz} \cdot \sqrt[3]{vz}}{\sqrt[3]{vx} \cdot \sqrt[3]{vx}} \cdot \left(\frac{\sqrt[3]{vz}}{\sqrt[3]{vx}} \cdot \left(bx - ax\right)\right)}\right)$
7. Final simplification0

$\leadsto -\left(\left(bz - az\right) - \frac{\sqrt[3]{vz} \cdot \sqrt[3]{vz}}{\sqrt[3]{vx} \cdot \sqrt[3]{vx}} \cdot \left(\frac{\sqrt[3]{vz}}{\sqrt[3]{vx}} \cdot \left(bx - ax\right)\right)\right)$

# Reproduce

herbie shell --seed 1
(FPCore (bz az vz vx bx ax)
:name "-((bz - az) - ((vz/vx) * (bx - ax)))"
:precision binary32
(- (- (- bz az) (* (/ vz vx) (- bx ax)))))